The Development Process of Nationalism and Patriotism in Kurdish Poetry: Functional-semantic and Artistic-literary Aspects - Farhad Mohammadi (پژوهشنامه ادبیات کردی)
The presence of a dominant and central theme in a nation's poetry signifies the historical progression of an idea through various stages and levels. These stages encompass diverse semantics and artistic expressions, highlighting the dynamic nature of ideas. In the context of Kurdish poetry, the idea of nationalism and patriotism can be observed to evolve through three distinct stages: the emerging stage, the evolutionary stage, and the peaking stage. At each stage, the idea of nationalism and patriotism in Kurdish poetry unfolds with distinct levels of functional-semantic and artistic-literary elements. Through the application of an analytical approach, this study aims to investigate the level at which nationalism and patriotism appear in each of these stages. According to the findings of the study, during the emerging stage, the functional-semantic aspect of the idea of nationalism and patriotism in Kurdish poetry is characterized by declarative elements, while the artistic-literary aspect maintains a level of simplicity and directness. As the idea progresses into the evolutionary stage, the artistic-literary aspect largely remains consistent with the previous stage in terms of simplicity and directness, while the functional-semantic aspect begins to shift towards centrality. Finally, in the peaking stage, the functional-semantic aspect of the idea reaches the level of discourse and centrality, accompanied by an artistic-literary aspect that showcases a higher level of artistic expression.